Compressive strain of la induced in ZnO nanorods by interstitial site passivation for enhanced charge carrier transport mechanism - Nurul Aliyah, Zainal Abidin; Faiz, Arith; Ahmad Syahiman, Mohd Shah; Sami, Ramadan; Ahmad Nizamuddin, Muhammad Mustafa; Nur Ezyanie, Safie; Mohd Asyadi, Azam; Marzaini, Rashid; Chelvanathan, Puvaneswaran (American Chemical Society, 2025)
Zinc oxide (ZnO) nanorods (NRs) doped with lanthanum (La) were synthesized via a low-temperature 90 °C hydrothermal method to investigate defect passivation and charge transport enhancement. Structural and spectroscopic characterization reveals that La3+ preferentially adsorbs at ZnO surfaces and grain boundaries, inducing compressive strain that suppresses defect formation without lattice substitution. Morphological studies demonstrate improved surface uniformity in La-doped NRs, while Raman spectroscopy shows reduced defect-related modes at 1 mol % La doping. XPS analysis confirms interfacial La3+ localization through characteristic 3.5 eV satellite features and minimal binding energy shifts of merely 0.2 eV. The optimal 1 mol % La-doped ZnO exhibits a conductivity of 5.46 S/m at 3.25 eV bandgap with a 4.6% improvement over high-temperature (>300 °C) synthesized La-ZnO references. While pristine ZnO shows higher absolute conductivity, these results demonstrate that low-temperature hydrothermal processing can achieve comparable electronic property enhancement to conventional high-temperature methods. This work provides fundamental insights into interfacial doping strategies for ZnO-based materials, with potential implications for optoelectronic applications.